Formation and characterization of nanoemulsion system containing hydrocortisone for transdermal application - Da Costa, Stephanie Sharon (2013)
Nanoemulsion is one of the most efficient dispersed delivery systems of particle size ranging in nano size. There are mainly two types of nanoemulsions; oil in water (O/W) and water in oil (W/O) nanoemulsion. O/W nanoemulsions were formulated to deliver hydrocortisone drug to the target site. The compositions were selected from the constructed phase diagrams. The addition of solvents gave a larger isotropic and homogeneous region in the ternary phase diagrams. Initially three type of solvents were selected, namely isopropanol (IPA), ethyl acetate (EA) and ethanol (EtOH). However due to the low solubility of hydrocortisone in ethyl acetate, it is not included in the phase diagram study. Phase diagrams of PKOEs/Lipoid S75:Tween 20 (60:40)/Water, PKOEs/IPA:Lipoid S75 (1:1)/Water:Tween 20 (60:40) and PKOEs/EtOH:Lipoid S75 (50:50)/Water:Tween 20 (60:40) systems were constructed at room temperature. It was observed that the PKOEs/IPA:Lipoid S75 (1:1)/Water:Tween 20 (60:40) and PKOEs/EtOH:Lipoid S75 (50:50)/Water:Tween 20 (60:40) systems showed improved solubility of water to give larger isotropic region compared to the PKOEs/Lipoid S75:Tween 20 (60:40)/Water system. A total of 9 compositions from the homogeneous region of the PKOEs/Lipoid S75:Tween 20 (60:40)/Water system were chosen because of the low surfactant concentration. The emulsions were then subjected to mechanical stirring for 4 hours to produce nano-sized emulsions which were then tested for accelerated stability (centrifugation). Nanoemulsion at point C (NEC) which exhibited highest stability was chosen for further studies. The influence of solvents and surfactant concentration to the stability and physical behavior of the palm based nanoemulsion was studied. The stability of the system was evaluated by measuring the particle size and zeta potential of nanoemulsion at room temperature over a period of 3 m. The mean droplet size for freshly prepared negatively charged nanoemulsions showed slight deviation. A decrease particle size was observed in nanoemulsions after solvent evaporation while particle size of nanoemulsions with different solvent concentration showed no significant difference. As for the positively charged nanoemulsions, the mean particle size of formulations decreased as the concentration of phytosphingosine was increased because phytosphingosine acts as a cosurfactant. All formulations except NEC[IPA:Lipoid (1:1)] SE and NEC[EtOH:Lipoid (1:1)] SE showed no significant difference in particle size. All formulations remain stable without visible phase separation in three different temperatures (5°C, room temperature and 45°C) for a period of 3 months. These findings showed that the presence of solvents increased the nanoemulsion stability thereby prolong the shelf life of the formulation. DSC thermograms showed no hydrocortisone peak for all the nanoemulsion samples prepared suggesting that hydrocortisone was dispersed in the nanoemulsions in an amorphous or non-crystalline state. The particle size measured in Transmission Electron Microscopy (TEM) was consistent with the size obtained using photon correlation spectroscopy. There was increment in size in the positively charged nanoemulsions as opposed to the negatively charged nanoemulsions. All the formulations were stable after undergoing heat-cool cycles, storage at 5°C, room temperature and 45°C for more than 12 months. The good stability was due to the high negative and positive surface charged induced by phytosphingosine. Biological activities of nanoemulsions were investigated using in vitro microbiological test. The results showed no bacterial growth in all nanoemulsions. This implied that the nanoemulsions have an antimicrobial effect against Escherichia coli. In vitro drug permeation results showed that the prepared nanoemulsions gave better drug release as compared to marketed hydrocortisone cream. This result further supports the claims of solvents as a penetration enhancer. Furthermore, histopathological studies illustrated that the formulated nanoemulsions did not cause any skin irritation, indicating that it is safe for human use. In conclusion, the nanoemulsion formulation is a promising vehicle for the delivery of hydrocortisone transdermally.